Development of Learning Video Media Using the Powtoon Application to Improve Literacy Skills - Dita Anggun Meirani; Rayendra Rayendra; Zelhendri Zen; Fetri Yeni (Postgraduate, University of Mataram, 2025)
An animated video learning medium utilizing the Powtoon platform was developed to strengthen literacy proficiency in Indonesian language education at the vocational high school level. Employing a Research and Development (R&D) framework with the ADDIE model, the study systematically proceeded through stages of analysis, design, development, implementation, and evaluation. A total of 70 tenth-grade students from SMK Negeri 2 Batam participated as purposively selected subjects. Expert validation and user assessments confirmed that the media met high-quality standards in content accuracy, visual appeal, and linguistic clarity. Students and teachers reported the platform to be intuitive and well-suited to the learning preferences of vocational learners. Quantitative analysis revealed a substantial increase in student achievement, with an N-Gain score of 0.53, placing it within the moderate-to-high improvement range. These results affirm that Powtoon-based animated learning not only enhances engagement but also significantly boosts literacy outcomes. The media presents a powerful pedagogical tool for modern classrooms, particularly in overcoming passive and text-heavy instructional barriers. Future research should explore its application to other language domains and broader educational contexts to assess its generalizability and long-term impact